Expressing a Z-disk nebulin fragment in nebulin-deficient mouse muscle: effects on muscle structure and function - Li, Frank (Skelet Muscle, 2020)
BACKGROUND: Nebulin is a critical thin filament-binding protein that spans from the Z-disk of the skeletal muscle sarcomere to near the pointed end of the thin filament. Its massive size and actin-binding property allows it to provide the thin filaments with structural and regulatory support. When this protein is lost, nemaline myopathy occurs. Nemaline myopathy causes severe muscle weakness as well as structural defects on a sarcomeric level. There is no known cure for this disease. METHODS: We studied whether sarcomeric structure and function can be improved by introducing nebulin’s Z-disk region into a nebulin-deficient mouse model (Neb cKO) through adeno-associated viral (AAV) vector therapy. Following this treatment, the structural and functional characteristics of both vehicle-treated and AAV-treated Neb cKO and control muscles were studied. RESULTS: Intramuscular injection of this AAV construct resulted in a successful expression of the Z-disk fragment within the target muscles. This expression was significantly higher in Neb cKO mice than control mice. Analysis of protein expression revealed that the nebulin fragment was localized exclusively to the Z-disks and that Neb cKO expressed the nebulin fragment at levels comparable to the level of full-length nebulin in control mice. Additionally, the Z-disk fragment displaced full-length nebulin in control mice, resulting in nemaline rod body formation and a worsening of muscle function. Neb cKO mice experienced a slight functional benefit from the AAV treatment, with a small increase in force and fatigue resistance. Disease progression was also slowed as indicated by improved muscle structure and myosin isoform expression. CONCLUSIONS: This study reveals that nebulin fragments are well-received by nebulin-deficient mouse muscles and that limited functional benefits are achievable.